A influência da variação das temperaturas mínimas na mortalidade por doenças circulatórias em Ituiutaba (MG) - Severino, Emmeline Aparecida Silva (2017)
The weather conditions are often pointed out as responsible for the worsening of illnesses, as well as ailments and symptoms manifested by the population. Based on this principle, Medical Climatology emerges with the main objective of understanding how the health / disease relationship develops under the perspective of the influence of climatic elements, trying to discover how this process directly and indirectly affects the population of a given place. The extreme climatic events, here considered as episodes or rhythms that go beyond what is expected, arise due to climatic variability, which is one of the most well known and studied aspects of climate dynamics. The influence and negative impact produced by this phenomenon have significant repercussions on human activities, disrupting the environmental and socioeconomic systems and, in the man himself, mainly on the health / disease relationship. In this sense, the present research aimed to investigate the influence of the minimum temperatures on the mortality by Stroke of people attended in the municipal health network of the city of Ituiutaba (MG). For this, the bibliographic survey of research on the theme of this research was first carried out. Soon after, the data on the climatic elements of the city on an hourly scale were collected from the automatic meteorological station belonging to the National Institute of Meteorology (INMET), during the winter period, being represented by the months of May, June, July and August of the Years from 2007 to 2014. Daily data on mortality from Cerebral Vascular Accident (CVA) were collected from the Municipal Health Department for the same period. In the attempt to validate the data collected, Pearson's Linear Correlation Coefficient was calculated for the analyzed months and episodes. It was possible to observe that the correlation between the minimum temperature variation on stroke deaths exists, although it is not significant. However, it is possible to observe in the graphs that, when there is a marked variation of the minimum temperatures in a short period of time, the death registry accompanies this variation, being in greater quantity when there is a marked variation. It is important to highlight that in addition to the influences that weather can exert on individuals, there are other variables that contribute to stroke mortality, being physiological, behavioral, genetic, socioeconomic, among others. It is important to highlight the importance of the work of this follow-up, which aims above all at expanding reference frameworks for future research and projects, as well as assisting public power in organizing and planning space in Ituiutaba (MG), in order to provide improvements for local population.